3D Animation Graphic Enhancing Process Effect Simulation Analysis. (22nd July 2022) - Liu, Bing; Liu, Huiying; Dung, Vinh Phuc
Abstract : Processing of graphics is the intermediate stage of an animated film. The adequacy of the preproduction preparation often requires the creators to repeatedly discuss a series of issues such as the story of the script, the structure of the play, the style of the art design and the setting of the scenes, the shape of the characters, and the style of the music. The study of the process of 3D animation graphics enhancing effect optimization can effectively improve the visual effect of images. The optimization of the effect of authenticity of 3D animation graphics requires the optimization of lighting of animation graphics, and the optimization of texture processing of images by extending the shadow map method to complete the optimization of the effect of authenticity of animation graphics. Image enhancement is a very important branch in the field of digital processing of graphics. It is a method of making some transformations to the information or data of an image by some strategy to make the region of interest more prominent in the image while suppressing the secondary information that does not need to be enhanced, with the ultimate goal of making the image conform to the visual response characteristics. It is in this context that this paper proposes to build a process of graphics simulation platform to simulate and analyze the effect of process of 3D animation graphics enhancing. The experimental results show that the enhancement of graphics reduces the running time by 16.5 s and 14.3 s compared to the CDD and FMM algorithms, respectively, and that the MSE and PSNR are both improved, indicating that the enhancement of graphics effectively improves the restoration effect while running quickly. Therefore, it is confirmed that the process of 3D animation graphics enhancing effect has a good balance to obtain a more desirable animation in 3D enhancement effect.